Unusual electronic transport in (1 − x)Cu2Se–(x)CuInSe2 hierarchical composites. Issue 20 (30th August 2022) - Chen, Yixuan; Zhang, Yinying; Lu, Ruiming; Bailey, Trevor P.; Uher, Ctirad; Poudeu, Pierre F. P.
Abstract : The hierarchical integration of Cu2 Se and CuInSe2 phases at nano- and micron-scale induces electronic band structure hybridization leading to a large increase in the electrical conductivity and carrier density of (1 − x )Cu2 Se/( x )CuInSe2 composites. Abstract : The ability to control the relative density of electronic point defects as well as their energy distribution in semiconductors could afford a systematic modulation of their electronic, optical, and optoelectronic properties. Using a model binary hybrid system Cu2 Se–CuInSe2, we have investigated the correlation between phase composition, microstructure, and electronic transport behavior in the synthesized composites. We found that both Cu2 Se and CuInSe2 phases coexist at multiple length scales, ranging from sub-ten nanometer to several micrometers, leading to the formation of a hybrid hierarchical microstructure. Astonishingly, the electronic phase diagram of the (1 − x )Cu2 Se–( x )CuInSe2 (15% ≤ x ≤ 100%) hierarchical composites remarkably deviates from the trend normally expected for composites between a heavily doped semiconductor (Cu2 Se) and a poorly conducting phase (CuInSe2 ). A sudden 3-fold increase in the electrical conductivity and carrier concentration along with a marginal increase in the carrier mobility is observed for composites at the vicinity of equimolar composition (48% ≤ x ≤ 52%). The carrier concentration increases from ∼1.5 × 10 20 cm −3 for the composites with x ≤ 45% to 5.0 × 10 20 cm −3 for x = 50%, and remains constant at 4.5 × 10 20 cm −3 with x value in the range of 52% < x ≤ 90%, then quickly drops to 8 × 10 18 cm −3 for pristine CuInSe2 phase ( x = 100%). The atypical electronic behavior was rationalized in the light of the formation of an inter-band (IB) within the band gap, which arises from the hybridization of native electronic point defects from both Cu2 Se and CuInSe2 phases in the resulting hierarchical composites. The result points to a new strategy to modulate the electronic structure of semiconductor composites to maximize interaction and coupling between two fundamentally contrasting properties enabling access to electronic hybrid systems with potential applications as interactive and stimuli-responsive multifunctional materials.